Human Rights Trials in Latin America: The Fujimori Trial in Comparative Perspective - Coletta Youngers (My University, 2016)
This document explores the trial of ex-Peruvian president, Fujimori, for charges of human rights abuses and corruption. This document explores this trial as the end of impunity for political leaders and the significance of this trial for the region.